Language, Politics, and Identity: an Interdisciplinary Investigation of Modern Political Discourse - M. A. Chigasheva; M. A. Yelizaryeva; V. A. Nagumanova; E. A. Makushkina (Дискурс профессиональной коммуникации, 2023)
The article discusses an interdisciplinary approach to the study of political discourse on the example of linguistic and political science studies devoted to the manifestation of national identity in the speeches of German politicians. The relevance is explained by the fact that the article for the first time considers the use of an interdisciplinary approach in the analysis of professional discourse by specialists from different scientific fields. The purpose of the work is to show how an interdisciplinary approach is implemented in the study of political discourse by linguists and political scientists. Both studies were carried out on the empirical material of 60 texts of public speeches by leading German politicians (H. Maas, Z. Gabriel, F.-W. Steinmeier, A. Merkel, O. Scholz, U. von der Leyen) at international and national events such as the Munich Security Conference, the UN General Assembly, government statements. Both studies used general scientific methods (description, analysis, continuous sampling method), as well as quantitative content analysis (political scientists) and statistical methods of the chi-square test and Cramer’s coefficient (linguists). The use of these methods led both research groups to approximately the same conclusions: German politicians tend to avoid emphasizing ethnic identity in their speeches on the international agenda, which is reflected in the language choices. The analysis by linguists of culture-bound elements with the help of the chi-square test showed that the elements of non-German realities predominate in the speeches. The content analysis carried out by political scientists revealed that the leading German politicians tend not to demonstrate their national identity, giving priority to positioning Germany as a member of the EU and NATO.